Survival of patients with thyroid papillary and follicular carcinoma: similarity and difference of prognostic factors (cohort retrospective study). - Guda, Bogdan (ScienceRise: Medical Science, 2019)
While analyzing the causes supposed to be important for disease prognosis and to impact on the patient’s survival of malignant thyroid tumors, the researches examine many factors. The aim of the study was to determine the indices of cumulative patients survival with differentiated thyroid carcinoma that belong to different histological types depending on biological properties of neoplasm and some clinical factors. Materials and methods: Retrospective study of the cohort of patients after surgical intervention. The information of patients (age and sex, histological type, size and categories of carcinomas (TNM), their invasive properties, the presence of multifocal growth), as well as the clinical characteristics of the disease (stage, volume of surgical intervention and radioiodine treatment, risk of relapse group, number of points in the system MACIS) was analysed. Results: In cases of papillary or follicular thyroid carcinoma the analyzed factors are important for further prognosis. The most essential factor for papillary carcinoma is the tumor size, which associated with other ones – metastasizing, multifocal growth, intra- and extra-thyroid invasion, relapse development. In patients below 45, which were operated because of cancer, without extra-thyroid tumor spreading and metastases, the favorable disease prognosis does not depend on the neoplasm type. Under other circumstances the impact of carcinoma histological type (for follicular carcinoma versus papillary ones) is more important, and in some cases – for men, for patients above 60, patients with tumors above40 mm, for multifocal neoplasm with intra- and especially extra-thyroid invasion, for cases of distant metastases, thyroidectomy with lymph nodes dissection, with relapses the histological tumor type, is extremely important. Conclusion: The obtained results confirm the conclusion that histological subtype of differentiated thyroid carcinoma, tumor size, age and patient gender are the most important predictor of diseases persistence/disease relapse or patients mortality